The aerodynamics and energy cost assessment of an able-bodied cyclist and amputated models by computer fluid dynamics - Forte, Pedro (2020)
Background andObjectives: The aim of this study was to assess and compare the drag and energy cost of three cyclists assessed by computational fluid dynamics (CFD) and analytical procedures. Materials andmethods: A transradial (Tr) and transtibial (Tt) were compared to a full-body cyclist at different speeds. An elite male cyclist with 65 kg of mass and 1.72 m of height volunteered for this research with his competition cloths, helmet and bicycle with 5 kg of mass. A 3D model of the bicycle and cyclist in the upright position was obtained for numerical simulations. Upon that, two more models were created, simulating elbow and knee-disarticulated athletes. Numerical simulations by computational fluid dynamics and analytical procedures were computed to assess drag and energy cost, respectively. Results: One-Way ANOVA presented no significant differences between cyclists for drag (F = 0.041; p = 0.960; η2 = 0.002) and energy cost (F = 0.42; p = 0.908; η2 = 0.002). Linear regression presented a very high adjustment for absolute drag values between able-bodied and Tr (R2 = 1.000; Ra2 = 1.000; SEE = 0.200) and Tt (R2 = 1.00; Ra2 = 1.000; SEE = 0.160). The linear regression for energy cost presented a very high adjustment for absolute values between able-bodied and Tr (R2 = 1.000; Ra2 = 1.000; SEE = 0.570) and Tt (R2 = 1.00; Ra2 = 1.00; SEE = 0.778). Conclusions: This study suggests that drag and energy cost was lower in the able-bodied, followed by the Tr and Tt cyclists.